A Study of the Effects of Using Matlab as a Pedagogical Tool for Engineering Mathematics Students - Mohammed, Abdul Majid; Huneiti, Zayed Ali; Balachandran, Wamadeva; Al-Naafa, Mohammed A. (International Journal of Online and Biomedical Engineering (iJOE), 2013)
The paper describes the effects of using MATLAB as a teaching and learning aid for engineering mathematics students. MATLAB has been integrated as a supplement to the traditional classroom teaching and learning. Students enrolled into the first year Integral Calculus course at the University of Haâ??il, Saudi Arabia, are the sample of the study. Students used the software in small groups and submitted their work in groups. The aims of the study are to assess the effects of the use of the software on studentsâ?? attitudes and motivation towards the utilization of technology in the teaching and learning of engineering mathematics and its impact on learning. Qualitative and quantitative data collected from the study revealed that the students have benefitted from the software. The use of the software has enhanced studentsâ?? conceptual understanding despite their weak mathematical skills. It has been noticed that studentsâ?? attitudes have been positive and their performance in the course has improved.